Client influence on valuation: Perceptual analysis of the driving factors - Amidu, Abdul Rasheed; Aluko, Bioye Tajudeen (International Journal of Strategic Property Management, 2010)
Recent behavioural real estate research effort on valuation bias judgement suggests that client influence is an important source of such bias. This paper, therefore, considers the theoretical potentials for client influence to bias valuations, and empirically analyse the factors impacting on the extent of influence client may exert on estate surveyors and valuers. To accomplish this aim, questionnaires were randomly administered to samples of estate surveyors and valuers in Lagos Metropolis. Using mean rating point, the survey ranked three factors; integrity of valuer or valuation firm, importance of the valuation outcome to the client and client size, as the most significant clients’ influencing factors. The results of the Chi‐square test did not, however, provide any statistical relationship between the size of firm, amount of experience and education of estate surveyors and valuers and their perception on the comparative importance of the identified clients’ influencing factors.First published online: 18 Oct 2010